Wikipedia und Geschichtswissenschaft - Rohwedder, Uwe (De Gruyter, 2015)
Historical scholarship and the digital humanities are still struggling to come to terms with the rise of Wikipedia, which has grown prodigiously in the last decade. Because of its enormous range, Wikipedia has made a significant impact on popular historical understanding. The contributors analyze Wikipedia as an external challenge to scholarship and sound out potential opportunities for collaboration with Wikipedia in research and teaching.